2018
DOI: 10.1002/ijgo.12719
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum vitamin D levels and preterm delivery among low‐risk parturients in Lagos, Nigeria

Abstract: Objective To determine the association between low maternal vitamin D levels and preterm delivery among parturients in Lagos, Nigeria. Methods The present study was an analytical cross‐sectional study of women with preterm deliveries (defined as <37 weeks) and women with term deliveries (defined as ≥37 weeks) at the labor unit of Lagos University Teaching Hospital between December 1, 2015, and October 31, 2016. Relevant information was obtained via a proforma, and maternal venous samples were collected immedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
1
10
0
1
Order By: Relevance
“…Reports indicate that about 15 million infants worldwide are born preterm [ 31 ]. Oluwole and co-workers demonstrated that pregnant women with vitamin D deficiency have an approximately 9-fold higher likelihood of preterm delivery [ 32 ]. Similarly, Kalok [ 33 ] observed a significant correlation between vitamin D level and gestational age at delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Reports indicate that about 15 million infants worldwide are born preterm [ 31 ]. Oluwole and co-workers demonstrated that pregnant women with vitamin D deficiency have an approximately 9-fold higher likelihood of preterm delivery [ 32 ]. Similarly, Kalok [ 33 ] observed a significant correlation between vitamin D level and gestational age at delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Reports indicate that about 15 million infants worldwide are born preterm [29]. Oluwole and co-workers demonstrated that pregnant women with vitamin D de ciency have an approximately 9-fold higher likelihood of preterm delivery [30].…”
Section: Discussionmentioning
confidence: 99%
“…Keterbatasan penelitian ini seharusnya terfokus kepada wanita reproduksi sehat sehingga peneliti menyarankan untuk selanjutnya perlu penelitian lanjutan tentang hipovitaminosis D dalam kehamilan dan kesehatan reproduksi. Penelitian Oluwole, Okunade, & Okojie (2019) Hasil statistik menunjukan prevalensi defisiensi vitamin D relatif rendah pada ibu melahirkan di Lagos-Nigeria dan ada kemaknaan secara statistik ibu hipovitaminosis D dengan persalinan prematur. Peneliti mengakui bahwa dalam penelitian ini dipilih populasi wanita yang berpendidikan dan cenderung melakukan diet yang kaya akan vitamin D dan nutrisi lain dibandingkan dengan wanita yang melahirkan di luar fasilitas kesehatan.…”
Section: Pembahasanunclassified